2016
DOI: 10.1016/j.neubiorev.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of metacognition: A critical perspective on current tasks

Abstract: Humans have a remarkable ability to reflect upon their behavior and mental processes, a capacity known as metacognition. Recent neurophysiological experiments have attempted to elucidate the neural correlates of metacognition in other species. Despite this increased attention, there is still no operational definition of metacognition and the ability of behavioral tasks to reflect metacognition is the subject of debate. The most widely used task for studying metacognition in animals, the uncertain-option task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…Because of their non-generality, these signatures are therefore not necessary conditions of Bayesian confidence. Furthermore, they may be observed under non-Bayesian models, indicating that they are also not sufficient conditions 10,14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of their non-generality, these signatures are therefore not necessary conditions of Bayesian confidence. Furthermore, they may be observed under non-Bayesian models, indicating that they are also not sufficient conditions 10,14 .…”
Section: Discussionmentioning
confidence: 98%
“…with increasing evidence discriminability, the relative frequency of low-confidence percepts increases while III Kepecs and Mainen 17 , Insabato et al 16 , and Fleming and Daw 11 call it the (folded) "X-pattern." IV Our finding is distinct from that of Insabato et al 16 , who show that the divergence signature would not be predicted under a non-Bayesian model in which the observer uses two measurements on each trial. Our analyses only concern Bayesian models in which the observer has a single measurement on each trial.…”
Section: Relevant Assumption In Hangya Et Almentioning
confidence: 99%
“…Nevertheless, a recent study suggested that the Bayesian calculation of the posterior probability of being correct does not necessarily imply the folded X-pattern [26]. The inverse is also not correct as the folded X-pattern does not necessary imply the Bayesian calculation of confidence [2729].…”
Section: Introductionmentioning
confidence: 99%
“…is also formalized in Moreno-Bote's (2010) model. Animal experiments on decision confidence have 26 received some criticism, primarily claiming that the tasks could potentially be solved without requiring any meta-cognition, for example, by treating tasks with a sure bet as a multi-alternative decision task (Insabato et al, 2016(Insabato et al, , 2017. However, Kepecs and Mainen (2012) pointed out that the same scrutiny should then also be applied to human tasks.…”
Section: Relationship With Decision Confidencementioning
confidence: 99%